Researching of spreading of radio waves from base stations of mobile communication inside of buildings - et. al., Haydar Madaminov Xudayarovich phd , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this article is to analyze the research devoted to propagation of radio waves inside the building, as well as conducting calculations radio channels located between the transmitting and receiving antenna. The approaches to determining the signal level radio channels inside and outside the buildings allow for a sufficient engineering calculations accurately calculate the attenuation of radio waves. The main objective in this case is the choice of an adequate model propagation in each case. at choice It affects a lot of factors: the frequency range, the distance mobile station from the base, the relief areas and parameters building. Most of the methods of calculation of the field inside the buildings is based on the a large number of experimental measurements in different buildings type, with different views of the walls of the material, floors, degree clutter furniture and equipment.